Ultrasound shear wave elastography for measuring intracompartmental pressure of compartment syndrome using a turkey hind limb model. (2nd January 2020) - Toyoshima, Yoichi; Webb, Jeremy; Gregory, Adriana; Fatemi, Mostafa; Alizad, Azra; Zhao, Chunfeng
Abstract: Diagnosis and treatment of acute compartment syndrome are quite challenging. It is well known that compartment pressure is an important factor for diagnosing fasciotomy. However, the current technology to measure the pressure using a needle-catheter is invasive and painful. Recently ultrasound elastography has been used to measure soft tissue elasticity based on shear wave propagation speed. Because the muscle's elasticity is affected by the pressure within the compartment, ultrasound elastography might be a possible tool for the compartment pressure evaluation. Ultrasound shear wave elastography and pressure were simultaneously measured using a clinical ultrasound system and clinically used catheter in a turkey anterior-lateral and anterior-deep compartment under elevated pressures of baseline, 10, 20, 30, 40, and 50 mmHg using vascular infusion technique. Shear wave propagation speed increased linearly in proportion to the increase in intra-compartmental pressure. Strong correlation was observed between measured pressure and mean shear wave speed in each compartment (anterior-lateral compartment, mean R 2  = 0.929, P < 0.001; anterior-deep compartment, mean R 2  = 0.97, P < 0.001). Compared with anterolateral compartment pressure, anterior-deep compartment pressure was the same at the baseline; however, it was significantly higher at intended anterolateral compartment pressures of 20 and 30 mmHg (P = 0.008, P = 0.016). By using ultrasound shear wave elastography, the compartment pressure can be accurately measured. This noninvasive technology can potentially help surgeons for the early detection, monitoring, and prognosis of intra-compartmental pressure.